Equilibrium Adsorption of Hexahistidine on pH-Responsive Hydrogel Nanofilms - Longo, Gabriel Sebastian (2014)
We present a molecular theory to study the adsorption of different species within pH-sensitive hydrogel nanofilms. The theoretical framework allows for a molecular-level description of all the components of the system, and it explicitly accounts for the acid-base equilibrium. We concentrate in the adsorption of hexahistidine, one of the most widely used tags in bio-related systems, particularly in chromatography of proteins. The adsorption of hexahistidine within a grafted polyacid hydrogel film shows a non-monotonic dependence on the solution pH. Depending on the salt concentration, the density of the polymer network, and the bulk concentration of peptide, substantial adsorption is predicted in the intermediate pH range where both the network and the amino acids are charged. To enhance the electrostatic attractions, the acid-base equilibrium of adsorbed hexahistidine is shifted significantly increasing the degree of charge of the residues, as compared to the bulk solution. Such shift depends critically on the conditions of the environment at the nanoscale. At the same time, the degree of dissociation of the network becomes that of the isolated acid-group in a dilute solution, which means that the network is considerably more charged than when there is no adsorbate molecules. This work provides fundamental information on the physical chemistry behind the adsorption behavior and the response of the hydrogel film. This information can be useful in designing new materials for the purification or separation/immobilization of histidine-tagged proteins.